Analisis Usability Portal Akademik Mika dengan Menggunakan Use Questionnaire - Rin Rin Meilani Salim; Yuni Marlina Saragih; Agustina Desi Ratnasari (Paradigma, 2022)
MIKA College X Academic Portal is a website designed to make academic administration easier for students and staff. This approach was designed to address time inefficiencies in academic administration for both faculty and students. MIKA not only simplifies academic administration tasks, but it also has capabilities that make reviewing students' Final Projects easier. The MIKA College X Academic Portal is available at all times and from any location. Because the usage of the MIKA academic portal is critical to the performance of higher education business operations, this research included a usability assessment that evaluated usefulness, ease of use, ease of learning, and satisfaction. USE QUESTIONNAIRE to access MIKA's academic portal. Based on the findings, it can be stated that the MIKA Academic Portal is fairly good in the eyes of its users, who include students, professors, and staff. This can be seen in the results, which show that on a scale of 1 to 7, the lowest value achieved is 5.67 and the highest value obtained is 6.47. The MIKA College X Academic Portal's usefulness measurement scores are 6.04 equals agree, ease of use is 5.85 equals agree, ease of learning is 5.97 equals agree, and satisfaction is 6.04 equals agree.